2013
DOI: 10.1111/jocs.12062
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Thrombectomy Using Video-Assisted Thoracoscopy

Abstract: We report a case of a 40-year-old male who had a left ventricular thrombus with impaired cardiac function. The thrombus was completely removed using a video-assisted thoracoscopy via a right mini-thoracotomy. This approach is less invasive, avoiding sternotomy and ventriculotomy which can cause postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…We have already reported that a minimally invasive approach through right minithoracotomy has several advantages, including less risk of fatal ventricular arrhythmia, surgical site bleeding, and mediastinitis by means of avoiding ventriculotomy and sternotomy [6]. In the present case, anticoagulation therapy was introduced within 3 hours after surgery, and early administration of an anticoagulant agent resulted in effective prevention of recurrent thrombus formation.…”
Section: Commentmentioning
confidence: 67%
“…We have already reported that a minimally invasive approach through right minithoracotomy has several advantages, including less risk of fatal ventricular arrhythmia, surgical site bleeding, and mediastinitis by means of avoiding ventriculotomy and sternotomy [6]. In the present case, anticoagulation therapy was introduced within 3 hours after surgery, and early administration of an anticoagulant agent resulted in effective prevention of recurrent thrombus formation.…”
Section: Commentmentioning
confidence: 67%
“…This was followed by semi-rigid endoscopes in four [7, 9, 21, 29], flexible endoscopes in three [2, 3, 30] and mixture of rigid and flexible endoscopes in one study [11]. In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35]. Other adjunct endoscopic instruments such as forceps, graspers, scissors, suckers or retractors were used in 13 studies [2, 3, 12, 13, 15, 19, 21, 25, 30, 32, 34, 35, 37].…”
Section: Resultsmentioning
confidence: 99%
“…In one case ventriculography was used [19] and in the remaining 22 cases the imaging method was not specified [1, 11]. In addition to pre-operative imaging with echocardiogram, in 10 cases intra-operative echocardiography was also used to ensure complete removal of the intracardiac lesions [9, 10, 12, 15, 21, 24, 2628, 31]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to conventional median sternotomy, it has the advantages of reduced bleeding, fewer blood transfusions, lower incidence of mediastinitis, shorter ICU stay, and faster recovery. Moreover, videoassisted right minithoracotomy allows determination of the AMLC shape and identification of intra-annular structures by direct view [5]. The safety and efficacy of MICS via minithoracotomy has been described in young patients with congenital heart defects and in patients with previous sternotomy [6,7].…”
Section: Discussionmentioning
confidence: 99%